On the macro-economic impact of bioenergy and biochemicals – Introducing advanced bioeconomy sectors into an economic modelling framework with a case study for the Netherlands. (January 2018) - van Meijl, H.; Tsiropoulos, I.; Bartelings, H.; Hoefnagels, R.; Smeets, E.; Tabeau, A.; Faaij, A.
Abstract: Advanced uses of biomass for bioenergy and biochemicals are being gradually introduced and are expected to grow considerably in regional economies, thus raising questions on their mid-term macro-economic impacts. To assess these impacts, we use a computable general equilibrium model and a regional energy systems model side-by-side. The former is extended with new sectors of lignocellulosic biofuels, bioelectricity, biochemicals, lignocellulosic biomass supply and tradeable pellets. Next to 1st generation biofuels and other renewable energy supply, the economic impacts of bioeconomy are assessed for technology development and trade openness scenarios. We demonstrate the macro-economic model by assessing developments of the Dutch bioeconomy in 2030. Under rapid technical growth and trade openness, the models consistently show increased biomass consumption and supply of bioenergy and biochemicals from lignocellulose through large-scale deployment of advanced biomass conversion technologies. Traditional fossil-based sectors are replaced by biomass, which brings additional macro-economic benefits on gross domestic product (0.8 bn€ a −1 ) and value added (0.7 bn€ a −1 ). Furthermore, it reduces projected decline in trade balance (0.7 bn€ a −1 ) and employment (2.5–4.5%) compared to low technology development. Extending the temporal scope to beyond 2030 may demonstrate additional macro-economic benefits of bioeconomy. This requires assessing the influence of improvements in the agricultural sector that may lower biomass prices, learning and other developments of promising biomass conversion technologies in the longer term. Uncertain fossil fuel and CO2 price developments necessitate additional sensitivity analysis. Highlights: Technological change and open trade lead to positive GDP contribution of bioeconomy. Technological change has a positive impact on trade balance and employment. High technology development leads to increased lignocellulosic biofuel and biochemical shares. A bioeconomy contributes modestly to meeting the Dutch emission reduction targets. More ambitious scenarios needed to meet climate targets (e.g. CO2 tax >100 $ t CO2 −1 ).